Assessment of Cyber Attacks Influence over Internet Network - Kajackas, A.; Rainys, R.; Aputis, A. (Elektronika ir Elektrotechnika, 2011)
The objective of the study is to prepare model to measure the impact of a cyber attack on the Internet network infrastructure, andidentify the weakness components of network. As a result of the study virtual Lithuanian Internet network model created and severaldifferent scenarios of cyber attacks prepared and tested. During the tests of the attack that generated traffic flood from international ASto the Lithuanian network infrastructure, 3 AS (nodes) and 4 interconnection lines was found that had the maximum subsequences.Other attacks targeting separate interconnection node of the network infrastructure, resulted that network was able to reroute the traffic.Ill. 6, bibl. 10 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.619